Peran Guru dalam Pelaksanaan Bimbingan Konseling - Sri Mulyati; Kamaruddin Kamaruddin (Program Studi Pendidikan Agama Islam STAI Auliaurrasyidin Tembilahan, 2020)
This study aimed to determine the role of teachers in the implementation of counseling guidance. The teachers' role in the implementation of counseling must able to involve parties in schools such as students, subject teachers, school principals, and parents so that the counseling program can be carried out properly because there are few things or problems that often arise during the school day. The role of the teacher in this study is the role of a guider, counselor, informant, facilitator, mediator, collaborator, organizer, motivator, director, initiator, transmitter, and evaluator in achieving educational success. This type of research is library research, the method used is qualitative descriptive, Data were analyzed narratively. The result showed that teachers carried out their roles by implementing a continuous process, voluntary nuances, guiding principles for both male and female students, implementing Eastern culture, and implementing effective and efficient implementation.